Hippocampus-Avoidance Whole-Brain Radiation Therapy Is Efficient in the Long-Term Preservation of Hippocampal Volume - Popp, Ilinca; Rau, Alexander; Kellner, Elias; Reisert, Marco; Fennell, Jamina Tara; Rothe, Thomas; Nieder, Carsten; Urbach, Horst; Egger, Karl; Grosu, Anca Ligia; Kaller, Christoph P. (Frontiers in Oncology, 2021)
Background and purpose: With improved life expectancy, preventing neurocognitive decline after cerebral radiotherapy is gaining more importance. Hippocampal damage has been considered the main culprit for cognitive deficits following conventional whole-brain radiation therapy (WBRT). Here, we aimed to determine to which extent hippocampus-avoidance WBRT (HA-WBRT) can prevent hippocampal atrophy compared to conventional WBRT. Methods and Materials: 35 HA-WBRT and 48 WBRT patients were retrospectively selected, comprising a total of 544 contrast-enhanced T1-weighted magnetic resonance imaging studies, longitudinally acquired within 24 months before and 48 months after radiotherapy. HA-WBRT patients were treated analogously to the ongoing HIPPORAD-trial (DRKS00004598) protocol with 30 Gy in 12 fractions and dose to 98% of the hippocampus ≤ 9 Gy and to 2% ≤ 17 Gy. WBRT was mainly performed with 35 Gy in 14 fractions or 30 Gy in 10 fractions. Anatomical images were segmented and the hippocampal volume quantified using the Computational Anatomy Toolbox (CAT), including neuroradiological expert review of the segmentations. Results: After statistically controlling for confounding variables such as age, gender, and total intracranial volume, hippocampal atrophy was found after both WBRT and HA-WBRT (p < 10-6). However, hippocampal decline across time following HA-WBRT was approximately three times lower than following conventional WBRT (p < 10-6), with an average atrophy of 3.1% versus 8.5% in the first two years after radiation therapy, respectively. Conclusion: HA-WBRT is a therapeutic option for patients with multiple brain metastases, which can effectively and durably minimize hippocampal atrophy compared to conventional WBRT.